Acid-Base Balance: Stewart’s Approach - Pradian, Erwin; Maskoen, Tinni Trihartini; Destiara, Andy Pawana (Majalah Anestesia dan Critical Care, 2015)
The Henderson-Hasselbalch approach to acid-base balance allows explanation and quantification of many disorders of acid-base phisiology and is still widely used in clinical practice. However, complex metabolic disorders, such as those present in critically ill patients, can be difficult to define and treat using this approach. Peter Stewart proposed a different approach to acid-base physiology based upon physicochemical principles, which are electrochemical neutrality, conservation of mass and law of mass action. According to Stewart, there are only three variables influence the dissociation of water. These independent variables are pCO2, total concentration of weak acid [ATot] and strong ion difference (SID). Another different is if in Henderson-Hasselbalch approach pointed on bicarbonat ion, Stewart use chloride ion as the important anion as the causatif factor so there are also known the terms hyperchloremia acidosis, dilutional acidosis and contraction alkalosis.